(untitled) (Revista de Ciências Agroveterinárias, 2005)
Hypocala andremona (Stoll, 1781) (Lepidoptera: Noctuidae) is the main pest of persimmon in Brazil. In this study, the suitability of artificial diets for rising this insect in the laboratory was evaluated and their biology on the natural host (persimmon leaves of the cultivar Fuyu) was examined, at a temperature of 26±1ºC, 70±10% RH and 12 hours day length. H. andremona did not complete the caterpillar stage when reared on artificial diets containing the following protein sources: white beans, wheat germ, soy bran, powdered skim milk and beer yeast (diet 1A); Carioca beans, wheat germ and beer yeast (diet 2A); and wheat germ and powdered skim milk (diet 3A). In these diets dehydrated persimmons, crystal sugar and/or inositol were used as phagostimulants. The addition of dehydrated persimmon to the diets increased the number of individuals of H. andremona that initiated the feeding activity. With diet 1C a greater number of caterpillars began the feeding activity (45.0%). Therefore, it is recommended to continue studies aiming to make this diet suitable for rearing H. andremona. The duration of the adult-egg-period of H. andremona on persimmon leaves of the cultivar Fuyu was 39.1 days and the total survival rate was 15.2%. Longevity was 15,6 and 16.8 days for males and females, respectively, and the medium fertility was 41.1 eggs/female. According to the table of fertility life, H. andremona shows a average duration of a generation (T) of 45.0 days. The net reproduction rate (Ro) demonstrated that the population of the insect can increase 34.05 times each generation. The innate capacity to increase in number (rm) was 0,07903 and the finite reason of increase (C) was 1.08224 females/female/day.